Dynamically triggered slip leading to sustained fault gouge weakening under laboratory shear conditions. Issue 4 (26th February 2016) - Johnson, P. A.; Carmeliet, J.; Savage, H. M.; Scuderi, M.; Carpenter, B. M.; Guyer, R. A.; Daub, E. G.; Marone, C.
Abstract: We investigate dynamic wave‐triggered slip under laboratory shear conditions. The experiment is composed of a three‐block system containing two gouge layers composed of glass beads and held in place by a fixed load in a biaxial configuration. When the system is sheared under steady state conditions at a normal load of 4 MPa, we find that shear failure may be instantaneously triggered by a dynamic wave, corresponding to material weakening and softening if the system is in a critical shear stress state (near failure). Following triggering, the gouge material remains in a perturbed state over multiple slip cycles as evidenced by the recovery of the material strength, shear modulus, and slip recurrence time. This work suggests that faults must be critically stressed to trigger under dynamic conditions and that the recovery process following a dynamically triggered event differs from the recovery following a spontaneous event. Key Points: In the lab instantaneous dynamic triggering requires fault gouge and dynamic strains exceeding 10−6 Following triggering there is a recovery process that takes place over multiple stick‐slip cycles We posit that similar processes may take place in situ